Optimizing carbon nanoparticle staining for sentinel lymph nodes in rabbit lower limb models: concentration and time dependence - Narbol Kylyshbek; Heng Wang; Shuning Feng; Yuxin Zhang; Dong Dong; Wangjaleoseop Han; Ayidana Ayoujiang; Liang Chen; Tianyi Liu (PeerJ, 2025)
Background and Objectives Carbon nanoparticles (CNPs) have been used as a lymphatic imaging agent that can selectively enter lymphatic vessels. This experiment used CNPs for lower limb lymph node staining in rabbits, aiming to explore the suitable concentration and time of CNPs for sentinel lymph node (SLN) sufficient staining, and the biosafety of CNPs retention was preliminarily explored. Methods Staining effect of SLN using different concentrations of CNP injection on the rabbit lower limb lymphatic model. To explore the temporal correlation of CNPs staining. We investigated the effects of long-term retention of CNPs in lymph nodes on lymph node tissue structure and mRNA expression of inflammatory factors (IL-6/TNF-α), apoptosis factors (Bcl-2/Bax), and fibrosis factors (Collagen-I/α-SMA). Results The lowest concentration to achieve adequate lymph node staining is 0.0781 mg/0.8 mL, while the best staining results were observed at least 12 hours post-injection. Long-term CNPs retention has no significant negative impact on the structure and function of lymph nodes. Conclusions CNPs are an effective and safe lymphatic tracer. It is a concentration-dependent and time-dependent lymphatic staining agent. 0.0781 mg/0.8 mL and 12 hours are suitable for the rabbit lower limb lymphatic staining model, which provides valuable data for further research on the application of CNPs in rabbit animal models. In addition, the results provide evidence for future clinical development of concentration and time standards for CNPs’ use.